46.2: Invited Paper: Micron‐Patterned Deposition through Shadow masks with high precision alignment for OLED and e‐Paper applications. Issue 1 (1st July 2013) - Ambrose, T.; Tamura, P.; Brocato, B.; Bucci, B.; Conrad, J.; Shelapinsky, J.; Sharma, P.; Little, S. Lauer and W.
Abstract: Conventional shadow‐mask alignment using mechanical pins or machine‐vision techniques achieve 5 micron alignment accuracy. Here we introduce a novel alignment system‐architecture based on coded apertures along with discrete photo detectors as the sensing elements. It allows submicron accuracy and repeatability making it highly suitable for display manufacturing applications.